The mGlu5 Receptor Protomer-Mediated Dopamine D2 Receptor Trans-Inhibition Is Dependent on the Adenosine A2A Receptor Protomer: Implications for Parkinson’s Disease - Romero-Fernandez, Wilber; Taura, Jaume J.; Crans, René A. J.; Lopez-Cano, Marc; Fores-Pons, Ramon; Narváez, Manuel; Carlsson, Jens; Ciruela, Francisco; Fuxe, Kjell; Borroto-Escuela, Dasiel O. (Springer, 2022)
The adenosine A2A receptor (A2AR), dopamine D2 receptor (D2R) and metabotropic glutamate receptor type 5 (mGluR5) form A2AR-D2R-mGluR5 heteroreceptor complexes in living cells and in rat striatal neurons. In the current study, we present experimental data supporting the view that the A2AR protomer plays a major role in the inhibitory modulation of the density and the allosteric receptor-receptor interaction within the D2R-mGluR5 heteromeric component of the A2AR-D2R-mGluR5 complex in vitro and in vivo. The A2AR and mGluR5 protomers interact and modulate D2R protomer recognition and signalling upon forming a trimeric complex from these receptors. Expression of A2AR in HEK293T cells co-expressing D2R and mGluR5 resulted in a significant and marked increase in the formation of the D2R-mGluR5 heteromeric component in both bioluminescence resonance energy transfer and proximity ligation assays. A highly significant increase of the the high-affinity component of D2R (D2RKi High) values was found upon cotreatment with the mGluR5 and A2AR agonists in the cells expressing A2AR, D2R and mGluR5 with a significant effect observed also with the mGluR5 agonist alone compared to cells expressing only D2R and mGluR5. In cells co-expressing A2AR, D2R and mGluR5, stimulation of the cells with an mGluR5 agonist like or D2R antagonist fully counteracted the D2R agonist-induced inhibition of the cAMP levels which was not true in cells only expressing mGluR5 and D2R. In agreement, the mGluR5-negative allosteric modulator raseglurant significantly reduced the haloperidol-induced catalepsy in mice, and in A2AR knockout mice, the haloperidol action had almost disappeared, supporting a functional role for mGluR5 and A2AR in enhancing D2R blockade resulting in catalepsy. The results represent a relevant example of integrative activity within higher-order heteroreceptor complexes.
Keywords: Parkinson, Enfermedad de; Dopamina - Receptores; Heteroreceptor complexes; Dopamine D2R receptor; Adenosine A2A receptor; Parkinson’s Disease; Metabotropic glutamate receptor subtype 5 (mGluR5); Oligomerization